In adaption of river continuum concept as correlation to macroinvertebrates functional feeding group in Cisadane Rivers headwater - Yunita Magrima Anzani; Majariana Krisanti; Yusli Wardiatno (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
River Continuum Concept (RCC) is an approach that describes the dynamic changes in the river system, the changes that occur are physical conditions (order of the river, canopy cover, and land use) and also the structure and function of communities. Functional feeding groups (FFG) of macroinvertebrates are related to environmental gradients in aquatic systems, including river ecosystem attributes. This study aimed to correlate the function of the macroinvertebrate communities with Cisadanes River headwater conditions based on RCC and also to estimate the attributes of the river ecosystem. This research was conducted in the headwaters of the Cisadane River, West Java-Indonesia. One of Cisadanes River headwaters was located in Mount Halimun-Salak National Park. Macroinvertebrates were collected from four sites inside the park (stations 1, 2, 3, and 4) and from two sites outside the park (stations 5 and 6). Collections were made twice a month, from April to June 2015 using a Surber sampler. The results showed that shredders and predators were relatively higher at stations inside the national park than at those outside the national park. While scrappers and collectors at stations located inside the national park were relatively lower than at stations outside the park. The value of the P/R ratio showed that all of the stations were heterotrophy. CPOM/FPOM ratio represents that shredder availability is high enough at stations inside the national park. While TFPOM/BFPOM ratio is slightly below the normal threshold value. HSI showed that the condition of the riverbed substrate stability is quite good. Composition changes of macroinvertebrates showed suitability with RCC. River ecosystem attributes and abiotic stream characteristics of Cisadanes River headwater support macroinvertebrate life and are in accordance with RCC.Keywords:EcologyMacroinvertebrateNational ParkRiparianRiver